Authority and authenticity in teachers' questions about literature in three contexts. Issue 2 (11th March 2022) - Levine, Sarah; Hauser, Mary; Smith, Michael W.
Abstract : Purpose: This study aims to explore the authentic questioning practices of English Language Arts teachers. Although language arts (LA) education emphasizes the value of authentic questions in discussions about literature, teachers still tend to ask known-answer questions that guide students toward one literary interpretation. However, outside their classrooms, teachers talk about literary texts from stances of openness and curiosity. Helping teachers recognize and draw on their out-of-school literary practices might help them disrupt entrenched known-answer discourses. The authors studied how the same teachers asked questions about literature in different settings. The authors asked: To what degree and in what ways did teachers' questions about literature change when they took on different roles in discussions of literature? Design/methodology/approach: Drawing on theories of classroom discourses and everyday practices, this study compared and analyzed types of questions asked by high school teachers as they took on three roles: teacher in the high school classroom, discussion leader in a professional development and everyday reader in discussion. Findings: Analysis showed that as participants moved further away from their teacher role, they were more likely to ask authentic, curiosity-driven questions that engaged fellow readers in exploratory, dialogic interpretation. They were less likely to attempt to maintain authority over students' interpretations. Research limitations/implications: The authors hope researchers will build on these explorations of teacher stances and language in different roles, so we can work toward disrupt entrenched known-answer discourses in the classroom. Practical implications: Drawing on this study's findings about questioning practices of participants in their role as reader (as opposed to discussion leader or classroom teacher), the authors suggest that teachers and teacher educators consider the following: First, teachers need to understand the power of interpretive authority and known-answer discourses and compare them explicitly to their own everyday practices through rehearsals and reflection. Second, teachers might focus less on theme and more on exploration of individual lines, patterns and unusual authorial moves. Finally, when preparing to teach, if teachers can reconnect with the stance and language of uncertainty and curiosity, they are likely to ask more authentic questions. Social implications: These findings suggest both the power of entrenched known-answer discourses to constrain and the potential power of making visible and drawing on teachers' literary reading practices in out-of-school contexts. Originality/value: To the best of the authors' knowledge, no studies have made an empirical comparison of the relationship between the role a teacher takes on during discussion and the kinds of questions they ask about literature. This study offers insight into the value of everyday curiosity and other out-of-school resources that teachers could – but often do not – bring to their facilitations of classroom discussions. The findings suggest that teachers, teacher educators and researchers must recognize and recruit teachers' everyday practices to the LA classroom.